The Norton anthology of English literature - Abrams, Meyer Howard, 1912-2015 (Norton, 1993)
The Sixth Edition of The Norton Anthology of English Literature continues to be the indispensable anthology. Like its predecessors, the Sixth Edition offers the best in English literature from the classic to the contemporary in a readable, teachable format. More selections by women and twentieth-century writers, a richer offering of contextual writings, apparatus fully revised to reflect today's scholarship, and a new larger trim size make the Sixth Edition the choice for breadth, depth, and quality. The Editors M. H. Abrams, General Editor, Emeritus, Cornell University E. Talbot Donaldson, Late of Indiana University Alfred David, Emeritus, Indiana University Hallett Smith, Formerly with The Huntington Library Barbara K. Lewalski, Harvard University Robert M. Adams, Late of University of California, Los Angeles George M. Logan, Queen's University Samuel Holt Monk, Late of the University of Minnesota Lawrence Lipking, Northwestern University Jack Stillinger, University of Illinois George H. Ford, Late of the University of Rochester Carol T. Christ, University of California at Berkeley David Daiches, Emeritus, University of Sussex Jon Stallworthy, Oxford University